1990
DOI: 10.1002/j.1556-6978.1990.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Roses, Ducks, and Doctoral Degrees in Counselor Education

Abstract: Points of agreement and disagreement with Randolph's article on changing the non‐psychology doctorate in counselor education are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In Maples et al's 1993 study, the number of applicants for each position dropped again to slightly below seven (6.92) per position. This decline supported the conclusion made by Maples (1 989) and advanced by Hollis and Wantz (1990), Wittmer and Loesch (1990). and Zimpfer and DeTrude (1990), that counselor education graduates have more career choices and that teaching is not necessarily the most attractive.…”
supporting
confidence: 74%
“…In Maples et al's 1993 study, the number of applicants for each position dropped again to slightly below seven (6.92) per position. This decline supported the conclusion made by Maples (1 989) and advanced by Hollis and Wantz (1990), Wittmer and Loesch (1990). and Zimpfer and DeTrude (1990), that counselor education graduates have more career choices and that teaching is not necessarily the most attractive.…”
supporting
confidence: 74%
“…Counselor education programs have expanded their offerings with such programs as community, mental health, substance abuse, and marriage and family counseling and therapy (Hollis & Wantz, 1990). As a result, there is an increase in the different number and types of career opportunities for graduates with counselor educator doctorates (Wittmer & Loesch, 1990;Zerface & Birch, 1974;Zimpfer & De-Trude, 1990). These increased career opportunities seem less important because salaries of doctoral degree holders are generally higher outside of higher education.…”
Section: Overviewmentioning
confidence: 99%
“…Research has found the doctoral degree in counselor education to be vital and unrivaled, producing well-trained students who provide a variety of services in the human relations field (Lanning, 1990;Vacc, 1990;Wittmer & Loesch, 1990). It is surprising, however, to note that even with evidence that over a 9-year period demand exceeded supply for counselor educators (Maples & Macari, 1998), a dearth of literature exists regarding doctoral students in counselor education programs (Boes, Ullery, Millner, & Cobia, 1999;Bruce, 1995).…”
mentioning
confidence: 99%
“…If counselor education doctoral students face academic and personal pressures, stress, isolation, and burnout and if they are uniquely educated and highly qualified (Altekruse, 1991;Council for Accreditation of Counseling and Related Educational Programs [CACREP], 1994;Kolbert, Brendel, & Gressard, 1997;Lanning, 1990;Rogers, Gill-Wigal, Harrigan, & Abbey-Hines, 1998;Schmidt, 1999;Vacc, 1990;Wittmer & Loesch, 1990), then research about the counselor education doctoral student is warranted. As Lanning has noted, "We will always be driven by the master's level education we provide, but that can only continue if we prepare quality doctoral level graduates" (p. 168).…”
mentioning
confidence: 99%